Agronomic and economic efficiencies of a partially acidulated rock phosphate on Brachiaria brizantha cv. Marandu in a forest soil in the Amazon region - Filho, Moacyr Bernardino Dias; Neto, Miguel Simão (Pesquisa Agropecuaria Brasileira, 1992)
The agronomic and economic effectiveness of a commercial source of partially acidulated rock phosphate (PARP), with 46% of the total P2O5 soluble in neutral ammonium citrate + water solution, was evaluated during 25 months, using single superphosphate (SSP) as the standard fertilizer, on a forest soil. The forage grass Brachiaria brizantha cv. Marandu was grown as the test crop. Both fertilizers were applied at the rates of 50 and 100 kg/ha of the total P2O5 and compared with a check (0 P2O5). The average PARP agronomic efficiency, calculated from the total P uptake was of 64%, and no increase was observed between the first and the last observation periods. The PARP proved to be less economical than the SSP to produce the same forage yields. The total P2O5 content of PARP should not be considered when estimating B. brizantha pasture fertilization, being the soluble P2O5 content a more appropriate basis.